Pro SharePoint Designer 2010 - Wright, Steve; Petersen, David (Apress, 2011)
SharePoint 2010 offers developers, designers, and users a sophisticated intranet, web application, and Internet site platform. But until now, SharePoint users have had to painfully edit code or seek developer assistance to customize more than just the most minor parts of their sites. All of that has changed with SharePoint Designer 2010. Gain complete control and enhance your SharePoint sites with a depth not previously possible using this book. Pro SharePoint Designer 2010 is your soup-to-nuts reference for unlocking the power of SharePoint Designer. Covering everything you'll need to know to create custom, rich SharePoint experiences, Pro SharePoint Designer 2010 is a masterful guide to getting the most from this powerful application quickly and easily. This book starts with a fast-paced introduction to the 2010 version of the SharePoint Designer solution, including an overview of its features and capabilities. Then, the authors demonstrate those tools in action in a practical, results-oriented way, showing you how to vastly improve the functionality, fit and finish of your SharePoint sites. With Pro SharePoint Designer 2010 at hand, you'll master the customization of the end user's complete SharePoint 2010 experience and be on your way to enhancing your sites in no t